IMPLEMENTASI FILSAFAT PERENNIAL DALAM PEMBELAJARAN - ., Nuryamin (Jurnal Pendidikan Kreatif, 2020)
Perenialisme a philosophy of education that is taken from the root of the word perennial or perennial which means growing continuously that runs according to the timeless time. So this view always believes in the existence of values, norms that grow in society, and are eternal in life. Values and norms inherent in culture that always exist in society as a result of human creativity, taste and initiative. Perennial philosophy views education as the process of guiding one's abilities (talents) to be active or real (real, manifested, and applied) as a basic human potential. In other words that humans have the same nature that originates from the origin of the event that is fitri with logical consequences on the nature of holiness and goodness. In Plato's view, humans basically have three basic potentials, namely lust, will and reason (mind). These three potentials are the basis for building human personality and character. These three potentials will grow and develop through education. Humans who have a large potential ratio will become the leader class humans, and high social class. Humans with great potential will, will become warrior humans, middle class. Humans with great potential for lust will become working people, the class of the common people. Education should be oriented towards developing the potential of reason to prepare students for the future.